Mastocytosis-derived extracellular vesicles exhibit a mast cell signature, transfer KIT to stellate cells, and promote their activation - Kim, Do-Kyun (Proc Natl Acad Sci U S A, 2018)
Extracellular vesicles (EVs) have been implicated in the development and progression of hematological malignancies. We thus examined serum samples from patients with systemic mastocytosis (SM) and found EVs with a mast cell signature including the presence of tryptase, FcεRI, MRGX2, and KIT. The concentration of these EVs correlated with parameters of disease including levels of serum tryptase, IL-6, and alkaline phosphatase and physical findings including hepatosplenomegaly. Given reports that EVs from one cell type may influence another cell’s behavior, we asked whether SM-EVs might affect hepatic stellate cells (HSCs), based on the abnormal liver pathology associated with mastocytosis. We found that KIT was transferred from SM-EVs into an HSC line eliciting proliferation, cytokine production, and differentiation, processes that have been associated with liver pathology. These effects were reduced by KIT inhibition or neutralization and recapitulated by enforced expression of KIT or constitutively active D816V-KIT, a gain-of-function variant associated with SM. Furthermore, HSCs in liver from mice injected with SM-EVs had increased expression of α-SMA and human KIT, particularly around portal areas, compared with mice injected with EVs from normal individuals, suggesting that SM-EVs can also initiate HSC activation in vivo. Our data are thus consistent with the conclusion that SM-EVs have the potential to influence cells outside the hematological compartment and that therapeutic approaches for treatment of SM may be effective in part through inhibition of effects of EVs on target tissues, findings important both to understanding complex disease pathology and in developing interventional agents for the treatment of hematologic diseases.